UiTM health fest 2025: breathe well, live well - Khairul Anuar, Ili Liyana; Zakiman, Zazarida; Yasin, Siti Munira; Selamat, Mohamad Ikhsan; Azhar, Zahir Izuan; Xin Wee, Chen (Faculty of Medicine, 2025)
A group of fourth- year undergraduate medical students under the guidance of Professor Dr. Siti Munira Yasin and Dr. Mohamad Ikhsan Selamat, successfully organised a community health promotion event at PPR Kg Baru Hicom on 24 August 2025. This initiative was held in collaboration with Majlis Bandaraya Shah Alam (MBSA), involving input from residents’ representatives.